Oral Healthcare Practices and Awareness among the Parents of Autism Spectrum Disorder Children: A Multi-Center Study - Abdullah Saad Alqahtani; Khalid Gufran; Abdulaziz Alsakr; Banna Alnufaiy; Abdulhamid Al Ghwainem; Yasser Mohammed Bin Khames; Rakan Abdullah Althani; Sultan Marshad Almuthaybiri (MDPI AG, 2023)
This study aimed to evaluate the knowledge and attitudes of the parents of autistic children toward oral health and the practice of oral hygiene habits. A questionnaire was constructed, validated, and distributed to the parents of autistic children at different autistic centers. The questionnaire was divided into three parts: demographic information on the parents of autistic children, the knowledge and attitudes of parents toward oral health, and the practice of oral hygiene habits in the current population. A total of 206 responses were collected. Irrespective of the parents' educational and employment statuses, most second children were diagnosed with autism, and most of the parents have four or more children. In terms of knowledge and attitudes toward oral health, a total of 90.30% of the patients were aware of the oral healthcare of their child, and 55.80% of parents take them to the dentist for checkups. Moreover, the response to the practice of oral hygiene habits from the parents was positive, and most of the parents assist in the oral hygiene practices of their autistic children. This study showed that most of the parents appeared to have satisfactory knowledge about oral health practices for autistic children. However, additional studies should also be conducted.